ZnFe2O4 Doped TiO2 Photocatalyst Synthesis and Characterization with Effect of Different Coupling Ratios on Band Gap - Iqbal, F. (Chemical Society of Pakistan, 2021)
In this work the effect of different coupling ratios of ZnFe2O4 and TiO2 on the band gap was investigated, to convert TiO2 as a visible light driven photocatalyst ZnFe2O4. In this work, ZnFe2O4 was synthesized utilizing sol-gel technique and calcining under normal atmosphere at 900 °C. Thereafter, ZnFe2O4 was coupled with TiO2 by mixing in 50 ml water in three different coupling w/w ratios (1:1, 1:2 and 2:1) followed by the calcination of coupled catalyst under nitrogen environment at 500 °C. XRD, XPS, FESEM-EDS imaging, TGA, UV-Vis, and FTIR were performed to characterize the catalyst. Crystal phase identification could be confirmed through XRD analysis with homogenous distribution of metal constituents through color mapping and surface charge transitions from XPS analysis for a better electron hole generation. Thermogravimetric analysis (TGA) confirmed that the pure ZnFe2O4 obtained at 900 °C, while FTIR verified the presence of desired functional group in ZnFe2O4. Moreover, Fourier Transformation Infrared Spectroscopy (FTIR) illustrated two major peaks and no extra major impurity was detected. ZnFe2O4 is visible light driven photocatalyst and TiO2 can work only under UV light. So, the effect of different coupling ratios of ZnFe2O4 with TiO2 was examined by UV-Vis characterization. The band gap is given by 1:1 was 2.8, 2:1 was 3.17 and 1:2 was 3.02. It was observed that the most optimum coupling ratio is 1:1 and the band-gap fall under visible region. The findings of this work could be supportive significantly for the selection of suitable coupling ratio to convert UV-driven photocatalyst into visible region active photocatalyst. © 2021 Chemical Society of Pakistan. All rights reserved.